2003
DOI: 10.1046/j.1468-2982.2003.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Depression and Anxiety, and Screening for Mental Disorders in Migrainous Patients

Abstract: The purpose of this clinic-based study was the assessment of symptoms of depression, anxiety, and non-specific psychiatric disorders amongst patients with migraine, compared with healthy subjects and with individuals with a non-neurological chronic disease. A cross-sectional study was carried out in which 178 individuals (migraine 51; psoriasis 35; healthy 92) were submitted to three scales: MADRS (depression), STAI-T (anxiety) and SRQ (screening for mental disorders). The subjects with migraine and psoriasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The difference between psoriasis and controls was greatest when using the HADS questionnaire (n ¼ 3 studies) with a pooled OR of 8.00 (95% CI 1.42-45.17). Only one study used the MADRS questionnaire and its primary objective was to EA Dowlatshahi et al compare depressive symptoms in migraine patients with those in psoriasis patients and healthy controls (Kowacs et al, 2003). In this study, depressive symptoms were not significantly elevated in the psoriasis group compared with the controls (OR 2.13, 95% CI 0.76-3.27; Table 2).…”
Section: Odds Of Depressive Symptomsmentioning
confidence: 68%
“…The difference between psoriasis and controls was greatest when using the HADS questionnaire (n ¼ 3 studies) with a pooled OR of 8.00 (95% CI 1.42-45.17). Only one study used the MADRS questionnaire and its primary objective was to EA Dowlatshahi et al compare depressive symptoms in migraine patients with those in psoriasis patients and healthy controls (Kowacs et al, 2003). In this study, depressive symptoms were not significantly elevated in the psoriasis group compared with the controls (OR 2.13, 95% CI 0.76-3.27; Table 2).…”
Section: Odds Of Depressive Symptomsmentioning
confidence: 68%
“…Concerning headaches and psychological symptoms, there was no statistical difference between psychological symptoms and headache types. In a study carried out by Kowacs and et al (63), a significant association of general psychiatric symptoms with migraine was found. The present data for the migraine group and TTH group also indicated that somatisation in both groups was significantly higher than that in the headache‐free group.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, patients were administered with BDI to address depressive features, which is a well-validated scale that has been used extensively in such populations before [10, 39]; this scale was not significantly affected by adding LCM. Anxiety is another one of the commonest complaints in patients undergoing antiepileptic therapy (see [3, 5]); we showed that STAI questionnaires, which explore anxiety trait and state and have been validated in several populations affected by chronic neurological illnesses [3941], are not modified by LCM add-on. However, it should be noted that both depressive and anxiety features at t 0 were slightly elevated in our patients as compared to control populations from our lab historical data (not shown).…”
Section: Discussionmentioning
confidence: 99%